Response of Calamagrostis angustifolia to burn frequency and seasonality in the Sanjiang Plain wetlands (Northeast China). (15th December 2021) - Gao, Chuanyu; Wang, Guoping; Santin, Cristina; Doerr, Stefan H.; Cong, Jinxin; Zhao, Hongmei
Abstract: Fire is an important disturbance in many wetlands, which are key carbon reservoirs at both regional and global scales. However, the effects of fire on wetland vegetation biomass and plant carbon dynamics are poorly understood. We carried out a burn experiment in a Calamagrostis angustifolia wetland in Sanjiang Plain (Northeast China), which is widespread wetland type in China and frequently exposed to fire. Using a series of replicated experimental annual burns over a three-year period (spring and autumn burns carried out one, two or three times over three consecutive years), together with a control unburned treatment, we assessed the effect of burn seasonality and frequency on aboveground biomass, stem density, and carbon content of aboveground plant parts and ground litter. We found that burning promoted plant growth and hence plant biomass in burned sites compared to the unburned control, with this effect being greatest after three consecutive burn years. Autumn burns promoted higher stem density and more total aboveground biomass than spring burns after three consecutive burn years. Burning increased stem density significantly, especially in twice and thrice burned plots, with stem densities in September over 2000 N/m 2, which was much higher than in the control plots (987 ± 190 N/m 2 ). Autumn burns had a larger effect than spring burns on total plant biomass and litter accumulated (e.g. 1236 ± 295 g/m 2 after thrice autumn burns compared 796.2 ± 66.6 g/m 2 after thrice spring burns), except after two burn treatments. With time since burning, total biomass loads increased in spring-burned plots, while autumn-burned plots showed the opposite trend, declining towards values found at unburned plots in year three. Our results suggest that, at short fire return intervals, autumn burns lead to a more pronounced increase in aboveground biomass and carbon accumulation than spring burns; however, the effects of spring burns on biomass and carbon accumulation are longer lasting than those observed for autumn burns. Highlights: A three-year burn experiment was carried out in a C. angustifolia wetland in China. Burning promotes plant growth with the greatest effect after three annual burns. DOC and MBC was more available and higher carbon mineralization rates in burned soils. Consecutive autumn burns promoted more aboveground biomass growth than spring burns. The effects of spring burning on biomass lasted longer than autumn burning.